Bringing Health Care Home: A Pilot Project to Improve Access to Primary Health Care Using Mobile Nurse Practitioner Services - Donna Clare (Athens Journal of Health and Medical Sciences, 2019)
In the last decade in Canada, goods and services delivered to one’s doorstep has become commonplace. In most major Canadian cities, anyone can easily arrange for food and drug delivery, massage and physical therapy, dental care and even dog grooming in one’s home. At the same time, primary health care provision in the community remains almost exclusively delivered in the clinic or facility setting, and within those services, health promotion and self-care education is notably sparse. One innovative organization in Calgary, Canada, has piloted a program to provide health care in clients’ homes. Services include comprehensive physicals and screening, prescribing, phlebotomy and specimen collection, wound care, referrals, counselling, and health promotion and self-care education for clients of all ages. Nurse Practitioners were chosen to provide these services based on their ability to provide the full spectrum of these health services. In addition to home visits, the Nurse Practitioners provide phone, video and email consultations depending on the situation, and access is 24/7. Pilot analytics include: Costs of the service, Cost savings to the public health care system, Client satisfaction, Nurse Practitioner satisfaction, Integration of health promotion and self-care, Comfort and use of multimedia (video, phone, email) by both clients and NPs, Challenges, Success stories.